Encapsulated Nanodroplets for Enhanced Fluorescence Detection by Nano‐Extraction. Issue 47 (26th October 2020) - Li, Miaosi; Cao, Rong; Dyett, Brendan; Zhang, Xuehua
Abstract: Enhancement of the detection signal of fluorescence microscopy in highly diluted solutions is of great importance in chemical analysis, sensing, and bioassay applications. Surface nanodroplets with atto‐ to femto‐liter volumes are promising tools for sensitive online detection by integrating their extremely efficient nano‐extraction and optical advantages. In this paper, the development of novel basic units of nanodroplets‐in‐a‐microdroplet by simple solvent exchange is reported. The encapsulated nanodroplets are applied for ultrasensitive and online detection in fluorescence imaging. The biphasic nature of the droplet composite enables simultaneous extraction and enrichment of both hydrophobic and hydrophilic compounds. Furthermore, the desirable lensing effect of the curved surface of the nanodroplets enhances the collection of light emitted from the fluorophore extracted in the droplets by ≈ 60‐fold, allowing sensitive and quantitative analysis of the fluorophore using fluorescence microscopy. The results highlight the potential of encapsulated nanodroplets as a simple and innovative method of signal enhancement in chemical analysis. By integrating selective concentration, extraction, and sensitive detection, the encapsulated nanodroplets reported here may have broad applications in many chemical and biological matrices. Abstract : Compartmentalized nanodroplets‐in‐a‐microdroplet structure are developed on surface by solvent exchange. The desirable lensing effect and nano‐extraction features of the encapsulated nanodroplets are applied for ultrasensitive and online detection in fluorescence imaging, achieving 60‐fold enhancement of the detection signal. The biphasic nature of the droplet composite enables selective enrichment and simultaneous detection of both hydrophobic and hydrophilic compounds.